Now it is summer - Spinelli, Eileen; DePalma, Mary Newell (Grand Rapids, Mich. : Eerdmans Books for Young Readers, 2011)
A young mouse is encouraged by his mother to enjoy summer while waiting for autumn to come.
2.5
K-3
K-3
Keywords: Autumn -- Juvenile fiction; Mice -- Juvenile fiction; Summer -- Juvenile fiction; Autumn -- Fiction; Mice -- Fiction; Summer -- Fiction; Autumn -- Fiction; Mice -- Fiction; Summer -- Fiction; Picture books for children